2014
DOI: 10.1093/humrep/det454
|View full text |Cite
|
Sign up to set email alerts
|

The CatSper calcium channel in human sperm: relation with motility and involvement in progesterone-induced acrosome reaction

Abstract: This work was supported by grants from Ministry of University and Scientific Research (Prin project to E.B. and FIRB project to S.M) and Regione Toscana (to G.F.). The authors have no conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
125
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(135 citation statements)
references
References 50 publications
9
125
1
Order By: Relevance
“…Furthermore, a previous study revealed that lead could inhibit voltage-dependent calcium channel currents in nerve cells (Busselberg et al 1991;Gawrisch et al 1997). In human spermatozoa, the voltagedependent calcium channel, CatSper, is regarded as the main channel to mediate Ca 2+ influx and regulate progesterone-induced acrosome reaction (Strunker et al 2011;Tamburrino et al 2014). Hence, lead treatment probably decreased [Ca 2+ ] i and inhibited the progesterone-induced acrosome reaction via a CatSper-related mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a previous study revealed that lead could inhibit voltage-dependent calcium channel currents in nerve cells (Busselberg et al 1991;Gawrisch et al 1997). In human spermatozoa, the voltagedependent calcium channel, CatSper, is regarded as the main channel to mediate Ca 2+ influx and regulate progesterone-induced acrosome reaction (Strunker et al 2011;Tamburrino et al 2014). Hence, lead treatment probably decreased [Ca 2+ ] i and inhibited the progesterone-induced acrosome reaction via a CatSper-related mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In human sperm, Ca 2þ influx is predominantly controlled by CatSper [28], which is closely associated with human sperm functions. It has been reported that CatSper expression correlates with human sperm motility [24]. Also, CatSper is regarded as the effector of progesterone and participates in the progesterone-induced acrosome reaction [24].…”
Section: Discussionmentioning
confidence: 99%
“…To further determine the underlying mechanism of ketamine caused sperm [Ca 2þ ] i decrease, followed by impaired human sperm functions, we examined the effect of ketamine on CatSper channel, because (1) CatSper is the sperm-specific and the predominant ion channel responsible for Ca 2þ influx, and it is associated with sperm motility [24]; (2) the sperm ability to penetrate through viscous medium is attributed to the activation of CatSper [14]; and (3) CatSper is involved in the progesterone-induced human sperm acrosome reaction [24]. To data, CatSper is a unique Ca 2þ channel that can use the patch-clamp technique for recording currents in human sperm [18].…”
Section: Ketamine Suppresses Human Sperm Catsper Currentsmentioning
confidence: 99%
“…Boar spermatozoa express the four subunits of the main sperm Ca 2+ channel (CatSper;Lishko et al 2011;Tamburrino et al 2014) in their plasma membrane. The CatSper becomes functional when boar spermatozoa are exposed to capacitation-inducing conditions; modulating sperm motility (Paper II).…”
Section: Discussionmentioning
confidence: 99%
“…Among the most important events regulated by sperm membrane proteins appear volume accomodation via AQPs [Tamburrino et al 2014] and opioid receptors [Agirregoitia et al 2006;) and the sperm-oocyte interaction and fusion via sperm membrane proteins (IZUMO1-JUNO, Aydin et al 2016;Ohto et al 2106). The main sperm membrane channels and receptors identified in pig, mouse and human spermatozoa are listed in Table 1.…”
Section: Sperm Membrane Proteinsmentioning
confidence: 99%